2013
DOI: 10.1080/08870446.2012.743128
|View full text |Cite
|
Sign up to set email alerts
|

Self-blame attributions, control appraisals and distress among cardiac rehabilitation patients

Abstract: This study examined associations between self-blame attributions, control appraisals and distress among cardiovascular disease patients participating in a cardiac rehabilitation (CR) programme. Questionnaire data were collected from 129 patients at the beginning and end of CR. We found little evidence that characterological self-blame (CSB) affects distress symptoms, but behavioural self-blame at the beginning of CR was positively associated with distress symptoms concurrently, and 12 weeks later. Furthermore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 22 publications
0
25
0
Order By: Relevance
“…For participants with cardiovascular disease (Bennett et al ., ), greater BSB was significantly associated with greater concurrent anxiety and depression. Greater BSB also significantly predicted increases in anxiety and depression over time when controlling for baseline levels of distress.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…For participants with cardiovascular disease (Bennett et al ., ), greater BSB was significantly associated with greater concurrent anxiety and depression. Greater BSB also significantly predicted increases in anxiety and depression over time when controlling for baseline levels of distress.…”
Section: Resultsmentioning
confidence: 97%
“…() also reported that 76% of those who did see themselves as blameworthy reported ‘mild–moderate’ self‐blame and 24% reported ‘high’ self‐blame. In other studies involving people with lung cancer, HIV/AIDS and cardiac disease, moderate levels were reported, with mean ratings corresponding to ‘agree – strongly agree’ (Mak et al ., ) and ‘somewhat – very much’ (Bennett et al ., ; Milbury et al ., ). Milbury et al .…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations